(untitled) (Acta Entomologica Serbica, 2014)
Gall Midges Gall Illustration Book (Diptera: Cecidomyiidae: Cecidomyiinae). The present paper cites 153 species out of 350 established in Serbia. The galls were collected and illustrated in a period of about 15 years, mostly in wider area of Belgrade. Herbarized plants with galls are stored in the collection “Herbarium cecidologicum Duške Simove” in the Natural History Museum in Belgrade. For each gall midge species the following data are given: host plant species and its family, valid name of the gall midge species and attacked plant part. The species are arranged by alphabetical order. Nomenclature of gall midge species is based on: SKUHRAVÁ (1986, 1989, 1997) and GAGNÉ (2004, 2010).